Application of lightweight aggregate and rice husk ash to incorporate phase change materials into cementitious materials. Issue 6 (1st November 2016) - Sharifi, Naser P.; Jafferji, Hajar; Reynolds, Savannah E.; Blanchard, Madison G.; Sakulich, Aaron R.
Abstract : Using phase change materials (PCMs) in buildings and pavements improves their thermal performance. However, PCMs cannot be directly added to cementitious media due to the interference of PCMs with hydration reactions. This study aims to evaluate the practicability of lightweight aggregate (LWA) and rice husk ash (RHA) to be used as PCM carrier agents in Portland cement-based mortars. The results show that LWA and RHA can absorb and contain liquids in their porous structures; and since these materials are compatible with cementitious media, they can be used as PCM carriers. However, a portion of the PCM may stick to the surface of the carriers or leak out of them and subsequently affect different properties of the binder. Incorporation of LWA presoaked in PCM decreased the compressive strength of the mortar by about 10%; however, when RHA was used as the carrier, the compressive strength was reduced by more than 35%.